The Civic Journalism / Public Journalism examined by one of its creators - Fernandes, Marcio (2019)
Davis Merritt is a legend in International Journalism. Legend in the best sense that the word can have. Author of four books (the most recent in 2015, called On life, liberty and the pursuit of perfect), has been at the top of American Journalism for more than four decades, working especially for the Knight Newspapers chain. He served as a professor at the University of Kansas and at Wichita State University. Between 1975 and 1997, he served as head of the Wichita Eagle, a diary in which he would make history, laying the foundations of what is now known as Civic Journalism (CJ), a proposal founded on the idea that, rather than simply denouncing life's problems in society, the journalist must think about solutions and, especially, stimulate citizen participation in collective life.In the following interview, Merritt shares invaluable information about this movement that emerged in the late 1980s, gained in the 1990s, and began to languish in 2000. In its maximum moment, the Civic Journalism was news and produced news in the US, Colombia , Bolivia, Argentina, Brazil, Portugal, Spain and many other countries. Merritt recalls the inaugural times (including highlighting the role of Jay Rosen, considered the other creator of CJ), clarifies the Civic Journalism / Public Journalism (more than 30 years after his initial concerns about Journalism's, so he prefers, as one perceives in all his answers) and thinks about the present time.On this issue Civic Journalism / Public Journalism (PJ), it is possible to emphasize what follows: all the questions made to Merritt make mention to the Civic Journalism, since this is the denomination better known in Brazil and in other places. As a matter of respect for the interviewee's opinion, we kept PJ in his responses. This duality is part of the richness of this talk about one of the most innovative ways of thinking and doing Journalism in the last 50 years.